2019
DOI: 10.1253/circj.cj-19-0065
|View full text |Cite
|
Sign up to set email alerts
|

Public-Access Defibrillation and Survival of Out-of-Hospital Cardiac Arrest in Public vs. Residential Locations in Japan

Abstract: Background: This study assessed whether the dissemination of public-access defibrillation (PAD) at the population level is associated with an increase in neurologically favorable outcomes among patients experiencing ventricular fibrillation (VF) in public vs. residential locations in Japan. Methods and Results: We enrolled adult patients with bystander-witnessed VF between 2013 and 2015. The primary outcome measure was 1-month neurologically favorable outcome defined by cerebral performance category 1 or 2. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(21 reference statements)
1
20
0
1
Order By: Relevance
“…Previous studies showed that public access AEDs and/or bystander CPR were more effective in public locations than in residential locations. 8,1517 In this study on prehospital CPR duration, patients with OHCA that occurred in public locations also had a higher proportion of one-month survival with favourable neurological outcome than those that occurred in residential locations. The predictive probability of favourable neurological outcome showed a higher proportion in public locations than in residential locations at any given time.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies showed that public access AEDs and/or bystander CPR were more effective in public locations than in residential locations. 8,1517 In this study on prehospital CPR duration, patients with OHCA that occurred in public locations also had a higher proportion of one-month survival with favourable neurological outcome than those that occurred in residential locations. The predictive probability of favourable neurological outcome showed a higher proportion in public locations than in residential locations at any given time.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies showed that public access AEDs and/or bystander CPR were more effective in public locations than in residential locations. 8,[15][16][17] In this study on prehospital CPR duration, patients with Figure 2. Non-linear relationship between the prehospital CPR duration and predictive probability of favourable neurological outcome using predictive margins in the univariable logistic regression model.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Japan, OHCA patients with public-access defibrillation had significantly better neurological outcomes compared with those without such facilities, while no significant differences in outcomes were identified for OHCA patients in residential locations 16 . ICD therapy could therefore help to reduce post-resuscitation encephalopathy with OHCA patients in residential locations, and the present data might have significant implications for the general clinical management of VF-OHCA.…”
Section: Relationship Between Mortality Of Vf-ohca and Icdmentioning
confidence: 88%